The Current State and Prospects for the Development of Academic Mobility in the Universities of the Republic of Kazakhstan - Sh. А. Yessimova; L. A. Khassenova (Экономика: стратегия и практика)
The main purpose of the article is to study the state and development prospects of academic mobility in Kazakhstani universities. Since the launch of mobility, the status of universities has changed significantly for the better, namely the quality of education has begun to increase, allowing to build up the capacity of graduates by studying foreign models, professional environment approaches competencies that will undoubtedly be in demand on the labor market. The current employers’ requirements for university graduates are very high, and only the presence of a systemic policy in universities for the development of various models of mobility will make it possible to comply with modern global trends. In the paper, the authors present the data of the Ministry of Education and Science of the Republic of Kazakhstan for 2019–2020, reflecting the activities of universities in the field of mobility, the data of the Auezov South Kazakhstan University. In 2020–2022 the conditions for mobility have been changed under the influence of economic and political factors and COVID-19. Overall, universities in most countries have switched to hybrid forms of study. The results of field research are presented to identify the role of mobility and efficiency of competencies, as well as the development skills of students on the example of the Auezov University. According to the study, it was concluded that mobility is an important factor in the preparation of competitive specialists for the economy of Kazakhstan. Undoubtedly, it impacts and plays an important role in the formation of the University 4.